Exploring Children’s Experiences Following Sport-Related Concussions: Identifying and Overcoming Emotional Challenges and Adversity Following Traumatic Brain Injury (TBI) - Mueller, Megan E.; Schmidt, Louis A.; Wright, Stephanie; Ali Raza, Insia; Patro, Gabriella; Rana, Mehwish; Volpe, Richard (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2022)
Objectives: To gain a better understanding of the emotional and mental experiences of child and adolescent athletes following a sport-related concussion, in order to better support these athletes throughout recovery. Methods: Adolescents (n=21) ages 15-24 years who self-reported experiencing a sport-related concussion under the age of 18, participated in a retrospective, single group, qualitative analysis based on semi-structured interviews. Thematic Content Analysis was used to identify themes amongst participants’ responses. Results: The results indicated three overarching domains with underlying themes and subthemes within: (1) Acute Challenges Post-Concussion (i.e., difficulty accepting unknowns, self-image and mattering, school, missing out and isolation, feelings of hopelessness), (2) Coping with Acute Challenges Post-Concussion (i.e., support, previous concussions, prioritizing mental health), and (3) Take-Aways Post-Concussion (i.e., learning about injury, self-growth, long lasting impacts on overall health). Conclusion: Child and adolescent athletes face numerous emotional challenges post-concussion and following recovery; however, there are many ways in which children are resilient and cope with these challenges. Implications: It is critical that the knowledge of child and adolescent athletes’ challenges post-concussion, as well as the successful coping mechanisms and protective factors utilized throughout recovery are used to develop better preventative and interventive strategies, in order to support the athletes’ well-being post-concussion.